Crystallization and preliminary X-ray crystallographic analysis of a bacterial Asn-transamidosome - Suzuki, Tateki (International Union of Crystallography, 2014)
Most canonical aminoacyl-tRNAs are synthesized directly by their cognate aminoacyl-tRNA synthetases (aaRSs), but glutaminyl-tRNA(Gln) and asparaginyl-tRNA(Asn) are synthesized indirectly by two-step processes. These processes are catalyzed by the transamidosome, a large ribonucleoprotein particle composed of GatA, GatB, GatC, aaRS and tRNA. In this study, the Asn-transamidosome from Pseudomonas aeruginosa was reconstructed and crystallized by mixing purified GatCAB complex, AspRS and tRNA(Asn). The crystal of the Asn-transamidosome belonged to space group P2(1), with unit-cell parameters a = 93.3, b = 186.0, c = 287.8 Å, β = 93.3°, and diffracted to 3.73 Å resolution. Preliminary X-ray crystallographic analysis showed that the asymmetric unit contained two Asn-transamidosomes, each composed of two GatCABs, one AspRS dimer and two tRNA(Asn)s, indicating that the construction of the current Asn-transamidosome differs from that of Thermus thermophilus.